A construção dos direitos: trabalhadores, associações e a legião cearense do trabalho (1931-1937) - Parente, Eduardo Oliveira (2020)
In 1931, the Legião Cearense do Trabalho (LCT) was created in Fortaleza, which won the support of a large contingent of workers and hegemonized, for some years, the workers' leadership in the capital of Ceará. In a context of strong concern with the so-called social issue, the LCT corporate project is understood as the result of the approximation between a Catholic militancy, informed in the principles of the Church's social doctrine, and the accumulated experiences of the heterogeneous groups of workers, gaining importance by articulating demands specific to the world of work and incorporating practices, traditions and representations that have long been built by workers. Through a wide variety of sources, the present research has as main objective to analyze the relationships established between different categories and the Legião Cearense do Trabalho in a process of struggle for rights, between 1931 and 1937, mainly. In this sense, we problematize documents produced by LCT, such as the booklet O Ideal Legionário and the weekly Legionário, the Encyclicals Rerum Novarum and Quadragésimo Anno, Minutes Books and other documents of some unions, a great diversity of periodicals of the first decades of the 20th century and of the final decades of the 19th century, official documents, such as Reports and Messages, criminal cases, laws, decrees, censuses, literary works, memoirs, chronicles, in addition to iconographic records and interviews. We verified the fundamental matrices of the LCT, based on a Catholic militancy and on the practices and traditions of the workers' groups, as well as the Legion's daily functioning. We analyzed associative growth in the early 1930s and disputes with other political currents, such as communism, and in relation to other corporate projects, such as Integralista and Varguista, in addition to highlighting the functioning of some unions. We identified the presence of workers in the city, tracking the characteristics of the population and the labor market, the ways of living, the forms of sociability and leisure. The strike processes carried out by various categories, especially in the years 1932 and 1933, a period of strong labor unrest in various parts of the country, are analyzed with emphasis on the demands, ideas, ways of acting and their importance in the construction and struggle for rights.